224 Digital Media Use and Sleep in College Students during COVID-19 Pandemic. (3rd May 2021) - Li, Winnie; Ye, Lichuan
Abstract: Introduction: To address the growing sleep deficiency epidemic in college students, more research is needed on recent factors that might affect sleep, such as the digital media use in this young adult population. Furthermore, sleep and the use of digital media can be heavily influenced by the COVID-19 pandemic. The purpose of this study is to examine the use of digital media during the pandemic, and its relationship with sleep disturbance, social isolation, physical and mental health in college students. Methods: An online survey was sent out to college students enrolled in an urban university. Validated questionnaires including PROMIS (Sleep Disturbance, Global Mental Health, Global Physical Health, Social Isolation), Nighttime Media Usage, and Internet Addition Test were included in the survey. In addition, focus groups were conducted with a subsample of survey respondents to elicit a comprehensive understanding of how digital media use in daily life influences sleep during the COVID-19 pandemic. Data collection was conducted during June to December 2020. Results: A total of 358 students completed the online survey. Sleep disturbance was significantly related to greater digital media use for recreational purposes two hours before bedtime (62.6±28.1 minutes, r=0.110, p=0.046), and a higher frequency of playing games (r=0.148, p=0.007) and using social media after going to bed (r=0.142, p=0.10). Sleep disturbance was significantly associated with social isolation (r=0.251, p<0.001), poor global physical health (r=-0.186, p<0.001) and mental health (r=-0.376, p<0.001), and lower GPA (r=-0.167, p=0.004). Additionally, seven focus groups were conducted in a total of 32 students, suggesting that the increase in free time from the COVID-19 pandemic led to greater digital media use, compromising sleep duration and quality. With the increase of screen time also came feeling of guilt and anxiety which often led to greater awareness and self-control around media use. Conclusion: Nighttime digital media use during the challenging pandemic time has a significant impact on poor sleep, which may lead to decreased academic performance, greater social isolation, and poor physical and mental health in college students. Effective interventions targeting digital media use are needed to improve sleep in this population. Support (if any):